Cyclic Electron Flow around Photosystem I Promotes ATP Synthesis Possibly Helping the Rapid Repair of Photodamaged Photosystem II at Low Light - Huang, Wei; Yang, Ying-Jie; Zhang, Shi-Bao; Liu, Tao (Frontiers in Plant Science, 2018)
In higher plants, moderate photoinhibition of photosystem II (PSII) leads to a stimulation of cyclic electron flow (CEF) at low light, which is accompanied by an increase in the P700 oxidation ratio. However, the specific role of CEF stimulation at low light is not well known. Furthermore, the mechanism underlying this increase in P700 oxidation ratio at low light is unclear. To address these questions, intact leaves of the shade-adapted plant Panax notoginseng were treated at 2258 μmol photons m-2 s-1 for 30 min to induce PSII photoinhibition. Before and after this high-light treatment, PSI and PSII activity, the energy quenching in PSII, the redox state of PSI and proton motive force (pmf) at a low light of 54 μmol photons m-2 s-1 were determined at the steady state. After high-light treatment, electron flow through PSII (ETRII) significantly decreased but CEF was remarkably stimulated. The P700 oxidation ratio significantly increased but non-photochemical quenching changed negligibly. Concomitantly, the total pmf decreased significantly and the proton gradient (ΔpH) across the thylakoid membrane remained stable. Furthermore, the P700 oxidation ratio was negatively correlated with the value of ETRII. These results suggest that upon PSII photoinhibition, CEF is stimulated to increase the ATP synthesis, facilitating the rapid repair of photodamaged PSII. The increase in P700 oxidation ratio at low light cannot be explained by the change in pmf, but is primarily controlled by electron transfer from PSII.